Improving agricultural soil health with feces-derived compost: a case study in northern Haiti - Bischak, Elena; Ward, Patrick; Jeliazovski, Julie; Remington, Claire; Bazile, Yamouch; Kramer, Sasha Bryn; Felix-Jean, Winnie; Ryals, Rebecca (Frontiers in Environmental Science, 2026)
Ecological Sanitation (EcoSan) may help achieve multiple United Nations Sustainable Development Goals, such as SDG 2, SDG 6, and SDG 13, through circular management of local biogeochemical cycles. However, more information on the impact of the land application of human excreta-derived fertilizers such as thermophilically co-composted human feces on soil health, soil carbon stocks, and crop yield is necessary in the areas where EcoSan products are utilized. We conducted a sorghum growth trial comparing feces-derived compost application to synthetic fertilization and an unfertilized control over two consecutive cropping cycles on a farm in northern Haiti. We found that feces-derived compost, particularly when overapplied on the basis of total nitrogen to account for its slow mineralization over time, led to increases in bioavailable soil micronutrients. Feces-derived compost application led to modest increases in carbon (C) and nitrogen (N) concentration in the same 0–10 cm soil layer by the end of the second sorghum crop cycle. No experimental treatments crop yields differed from unfertilized soil in either cropping cycle. This research contributes to our understanding of the full life cycle benefits of source-separated sanitation strategies by showing short-term soil health and fertility benefits from the use of EcoSan compost.